Menakar Aspirasi Pengaduan Online Rakyat di Bali (Studi pada Pemerintah Kabupaten Badung) - I Made Utama Jaya Wiguna; A.A.N. Eddy Supriyadinata Gorda (Program Studi Administrasi Negara Universitas Serang Raya, 2021)
Public complaint management is one of the important aspects in improving the quality of public services in an area. In Badung Regency, local public complaint management has been integrated into the People's Online Complaints Aspiration Service (LAPOR) program. This study aims to determine the effectiveness of the implementation of handling public complaints through the LAPOR program. The method used in this research is descriptive with a qualitative approach, with data collection techniques used are interviews and documentation. The results showed that the socialization carried out by the LAPOR management team in Badung Regency was still not optimal, because there were still many people who did not understand or know the flow of public complaints through the LAPOR program. This research is also expected to make the public more familiar with the LAPOR application and can directly and actively submit complaints or things that they feel need to be improved in public services in Badung Regency.